1998
DOI: 10.1111/j.1399-6576.1998.tb05159.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of esmolol on haemodynamic response to CO2 pneumoperitoneum for laparoscopic surgery

Abstract: Esmolol blunts the pressor response to induction and maintenance of pneumoperitoneum and may protect against renal ischaemia during pneumoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 34 publications
2
79
1
2
Order By: Relevance
“…2 Various drugs like opioids, ß blockers, nitroglycerine, magnesium sulphate etc. [3][4][5] have been tried to attenuate the PNP-associated haemodynamic instability but with limited success.…”
Section: Introductionmentioning
confidence: 99%
“…2 Various drugs like opioids, ß blockers, nitroglycerine, magnesium sulphate etc. [3][4][5] have been tried to attenuate the PNP-associated haemodynamic instability but with limited success.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos observaram um aumento na concentração plasmática do hormônio antidiurético (ADH) após a criação do pneumoperitônio 40,50,51 , suficiente para determinar o aumento da PAM e da SVR por vasoconstrição 40,52,53 . Acriação do pneumoperitônio com a insuflação de CO 2 leva a um aumento da concentração plasmática da renina [54][55][56] e da aldosterona 55 e da noradrenalina. Um estudo não observou alterações significativas nas concentrações da epinefrina, da norepinefrina e na atividade da renina plasmática, que pudessem estar correlacionadas ao aumento da PAM 40 .…”
Section: Resultsunclassified
“…Some studies have observed increased plasma concentration of antidiuretic hormone (ADH) after pneumoperitoneum 40,50,51 , enough to determine increased MBP and SVR by vasoconstriction 40,52,53 . CO 2 pneumoperitoneum leads to increased rennin [54][55][56] , aldosterone 55 and norepinephrine plasma concentration. A study has not observed significant epinephrine and norepinephrine concentrations, and plasma rennin activity changes which could be related to increased MBP 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Koivusalo et al, in their study, have shown that postoperative recovery after laparoscopic cholecystectomy was faster and uneventful when carbon dioxide was not used for pneumoperitoneum. They suggested that mechanical abdominal lift method without carbon dioxide insufflations is better for laparoscopic cholecystectomy may be the method of choice while considering laparoscopic cholecystectomy [10] . Fenton et al, in their review, observed that moxonidine acts centrally to reduce central and peripheral sympathetic activity, thus decreasing peripheral vascular resistance.…”
Section: Discussionmentioning
confidence: 99%